Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1038/sj.jcbfm.9600173
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effect of PARP-2 Deletion on Brain Injury after Focal and Global Cerebral Ischemia

Abstract: Poly(ADP-ribose) polymerase-2 (PARP-2) is a member of the PARP enzyme family, and, similarly to PARP-1, catalyzes the formation of ADP-ribose polymers in response to DNA damage. While PARP-1 overactivation contributes to ischemic cell death, no information is available regarding the role of PARP-2. In this study, we evaluated the impact of PARP-2 deletion on histopathological outcome from two different experimental models of cerebral ischemia. Male PARP-2 À/À mice and wild-type (WT) littermates were subjected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 37 publications
(83 reference statements)
2
47
0
Order By: Relevance
“…It is highly important to customize therapy after a hypoxia situation at birth followed by resuscitation in regard to insult severity and timing, which can be monitored both by imaging and biomarkers. The alteration of cell death pathways and response to neuroprotective strategies seem to have different effects on focal vs. global hypoxia (20), with the latter being independently able to induce oxidative injury in the cerebral cortex (21). Nevertheless, the hypoxia-reoxygenation model is a milder oxidative insult than HI, and there is evidence that this hypoxia-provoked oxidative stress can be counteracted by central nervous system protective mechanisms (22).…”
Section: Discussionmentioning
confidence: 99%
“…It is highly important to customize therapy after a hypoxia situation at birth followed by resuscitation in regard to insult severity and timing, which can be monitored both by imaging and biomarkers. The alteration of cell death pathways and response to neuroprotective strategies seem to have different effects on focal vs. global hypoxia (20), with the latter being independently able to induce oxidative injury in the cerebral cortex (21). Nevertheless, the hypoxia-reoxygenation model is a milder oxidative insult than HI, and there is evidence that this hypoxia-provoked oxidative stress can be counteracted by central nervous system protective mechanisms (22).…”
Section: Discussionmentioning
confidence: 99%
“…Depletion of PARP-2 also resulted in a protective phenotype against diseases associated with increased oxidative stress. Genetic deletion or silencing of PARP-2 has provided protection in models of focal and global cerebral ischaemia [99,100], colitis [59] and doxorubicin-induced vascular smooth muscle damage [33]. Since PARP-2 accounts for a small fraction of total cellular PARP activity [8,32,33], it is unlikely that the ablation of PARP-2 could protect against the loss of cellular NAD + and ATP suggesting different mechanisms of cell death as compared to the case of PARP-1 ablation.…”
Section: Parp-2 In Oxidative Stress-related Diseasesmentioning
confidence: 99%
“…These nonactively growing cells are therefore more sensitive to inhibition of the mitochondrial respiratory chain. The decision between cell death and survival after exposure to necrosis-inducing agents is regulated mainly by the availability of metabolic substrates and the expression levels or enzymatic activities of PARP-1 and, in part, PARP-2 (47,205,468). Thus, there is clear evidence that poly-ADP-ribosylation reactions play a central role in "programmed necrosis" pathways (47,113,449,468).…”
Section: Adp-ribosylation Reactions In Cell Death Processesmentioning
confidence: 99%
“…Recent studies demonstrated that the cellular metabolic status is a key factor in determining how ATP levels are affected by overstimulation of poly-ADP-ribosylation reactions (449,468). The massive generation of poly-ADP-ribose in the nucleus by overactivation of PARP-1 and, to a lesser extent, PARP-2 was suggested to preferentially deplete the nuclear and cytosolic pools of NAD ϩ but not the mitochondrial pools, thereby inhibiting glycolysis but not oxidative phosphorylation (205,468). Actively proliferating cells use glucose almost exclusively through aerobic glycolysis for the production of ATP and die from NAD ϩ and ATP depletion resulting from overactivation of poly-ADP-ribosylation.…”
Section: Adp-ribosylation Reactions In Cell Death Processesmentioning
confidence: 99%